2014
DOI: 10.1111/jvs.12231
|View full text |Cite
|
Sign up to set email alerts
|

Performance of late succession species along a chronosequence: Environment does not exclude Sphagnum fuscum from the early stages of mire development

Abstract: Questions: Sphagnum fuscum (Schimp.) Klinggr. is a characteristic species of the later stages of mire development. It is hypothesized that competition limits its success in earlier successional stages where higher mineral nutrient availability and wetter conditions favour species with a higher production rate and, therefore, a stronger ability to compete. We aim to quantify the importance of different site factors and the effect of neighbouring plants on the performance of S. fuscum.Location: A mire chronosequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Secondly, in habitats with a more persistently high moisture content, such as lawns and hollows, interspecific competition becomes important: it is acknowledged that species from such habitats generally have higher growth rates and photosynthetic capacity than hummock species (e.g. Laing et al, 2014;Bengtsson et al, 2016). Our results also agreed with this, as setting the growth-related parameters (i.e.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Secondly, in habitats with a more persistently high moisture content, such as lawns and hollows, interspecific competition becomes important: it is acknowledged that species from such habitats generally have higher growth rates and photosynthetic capacity than hummock species (e.g. Laing et al, 2014;Bengtsson et al, 2016). Our results also agreed with this, as setting the growth-related parameters (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…1b). The light levels were chosen based on previous investigation by Laine et al (2011Laine et al ( , 2015, which showed increasing A until PPFD at 1500 and no photoinhibition even at high values of 2000 µmol m −2 s −1 . The samples were allowed to adjust to cuvette conditions before the first measurement and after each change in the PPFD level until the CO 2 rate had reached a steady level, otherwise the cuvette conditions were kept constant (temperature 20 • C, CO 2 concentration 400 ppm, flow rate 500 µmol s −1 , impeller at level 5, and relative humidity of inflow air 60 %, although the relative humidity remained on average 81 % during the measurements).…”
Section: B2 Measurement Of Photosynthetic Traitsmentioning
confidence: 99%
“…The resistance we observed is likely linked to bogs’ dependence on rainfall for both moisture and nutrients (Nijp et al., ) making especially hummocks naturally exposed to seasonal droughts and extremely nutrient‐limited conditions (Rydin & Jeglum, ). Bog vegetation is already adapted to survive in very restrictive conditions and can persist despite the WLD with adaptations such as nutrient recycling (Laine, Ehonen, Juurola, Mehtätalo, & Tuittila, ; Small, ). The mechanism of our treatment (lowering the water table from the peat surface and not controlling precipitation) and the hydrological regime of a bog (precipitation‐driven), may partly explain the resistance found for the ombrotrophic site.…”
Section: Discussionmentioning
confidence: 99%
“…Bog vegetation is already adapted to survive in very restrictive conditions and can persist despite the WLD with adaptations such as nutrient recycling (Laine, Ehonen, Juurola, Mehtätalo, & Tuittila, 2015;Small, 1972). The mechanism of our treatment F I G U R E 3 Response of different plant communities (Appendix S5: (2000, 2001, 2002, 2003, 2009, and 2016 (lowering the water table from the peat surface and not controlling precipitation) and the hydrological regime of a bog (precipitation-driven), may partly explain the resistance found for the ombrotrophic site.…”
Section: Impact Of Wldmentioning
confidence: 99%
“…The measured light levels were 2000, 25 and 0 µmol m −2 s −1 for vascular plants and 2000, 35 and 0 µmol m −2 s −1 for Sphagna. Light levels were designed to catch both the linear, light-limited beginning and the light-saturated maximum of the light response curve without causing photoinhibitory reduction of photosynthetic rate (Laine et al, 2015). Vascular plants were measured with a standard cuvette, but for Sphagna we used a moss cuvette of our own construction with internal dimensions of 3 × 2 × 1 cm (Hájek et al, 2009) with a net bottom to allow airflow above and below the sample reducing the aerodynamic resistance.…”
Section: Plant Level Photosynthesis Measurementsmentioning
confidence: 99%